Even function: f(-x) = f(x). If you replace x by -x you should find the same function.
Odd function: f(-x) = -f(x). If you replace x by -x you find the same function with opposite sign;
Is f(-x) = f(x)?
f(x) = (x+4)² = x² + 8x +16
f(-x) = (-x+4)² = x² - 8x + 16, then it's not an even function
Is f(-x) = -f(x)?
f(-x) = (-x+4)² = x² + 8x + 16 , then it's not an odd function
It is neither an even nor an odd function
These are like terms, meaning that they are completely the same disregarding the coefficient.
To combine like terms, add the coefficients.
16+(-12)=4
Final answer: 4x
Answer:
Step-by-step explanation:
If there are 9 marbles in total and the desired outcome is to pick a green marble then the probability is = which simplifies down to a third.
Answer:
Step-by-step explanation:
<u>We can't multiply.</u>
<u>We got to count up by 12's for each 1/2 hour.</u>
12, 24, 36, 48, 60, 72, 84, 96, 108, 120, 132, 144, 156, 168.
<u>Simplified:</u>
- 24, 48, 72, 96, 120, 144, 168.
<u>Estimate:</u>
- 12 = 1/2 hour
- 24 = 1 hour
- 36 = 1 1/2 hours
- 48 = 2 hours
- 60 = 2 1/2 hours
- 72 = 3 hours
- 84 = 3 1/2 hours
- 96 = 4 hours
- 108 = 4 1/2 hours
- 120 = 5 hours.
- 132 = 5 1/2 hours
- 144 = 6 hours
- 156 = 6 1/2 hours
- 168 = 7 hours.
Answer is 168.
To do this problem you would first need to factor out a variable, which in this case I would want to do the first equation because it is isolated. Now the equations would look like this:
x = -2y - 1
4x - 4y = 20
Since we know that x is now equal to -2y - 1 we can plug it in to the x value in the second equation:
4 (-2y -1) - 4y = 20
-8y -4 - 4y
-12y - 4 = 20
-12y = 24
y = -2
Now that we know the y value plug the y value to one equation to find the x, I will be using the first equation
x + 2(-2) = -1
x - 4 = -1
x = 3
Solutions:
y = -2
x = 3